The existence and the shape of the equilibrium strategies for some two-person non-zero sum games with the choice of the moment - Sūdžiūtė, D. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Д. П. Суджюте. Существование и вид равновесных стратегий некоторых не антагонистических игр двух лиц с выбором момента времениD. Sūdžiūtė. Kai kurių neantagonistinių dviejų asmenų lošimų su laiko momento parinkimu pusiausvyros strategijų egzistavimas ir pavidalas